PROBLEM OF PERMISSIBILITY OF FIDUCIARY TRANSFER OF PROPERTY IN OUR LAW – PROPOSALS DE LEGE FERENDA - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Institut or fiducia comes from Roman law, and is most often used for fiduciary transfer of property to manage assets (fiducia cum amico contracta) and the fiduciary transfer of property in order to secure receivables (fiducia cum creditore contracta). Fiduciary transfer of property rights is reaffirmed due to visible advantages over other security claims. The most important advantage of fiduciary agreements compared to a lien security is reflected in a much faster collection of receivables, since, this shortens lengthy court procedures. Fiducijant or borrower from basic contract, at the time of conclusion of the agreement transfers ownership of the property to the trustee or creditor. Unlike the lien, where it is impossible, in case of fiduciary borrower agreement object of security can remain in the possession of creditor, and is used, inter alia, for the recovery of the creditor. Divergence of legal form and economic content is typical for this institute, and some theorists, such as Gams, reinforce the belief that such legal transactions are illegal. National courts very often declare fiduciary transfer of property as forbiden, subsuming it under a ban of lex commissoria. However, the prevailing attitude of Serbian civilistike is that the institution of fiduciary agreements is allowed because it is not contrary to the general prohibition of violation of compulsory regulations, public order and good customs. Fiduciary agreements are not regulated by applicable legal regulations in Serbia. Some authors believe that, after the institute of the mortgage of the movable property entered in register has became the parte of our legal system – reasons for the legal regulation of fiduciary transfer of property no longer exist. The author of this article disagrees with this position and advocates for the incorporation of this institute in Serbian laws, both because the fiduciary transfer of property is suitable for the creditor than the non-possessory lien, and because of the fact that this institution already exist in the legal practice. Parties that secure their claims in this way often encounter a lack of understanding and of the courts, and that is why they are brought into a situation of legal uncertainty. Institute “fiducia cum amico contracta” has also experienced a reaffirmation in some continental legal systems. Author of this article is of the view that this institute would have beneficial effects on legal market and further development of economic relations in Serbia.